Comparison of Adequacy of Reduction of Third Malleolar Fracture in Prone vs. Spine Position in Tri-Malleolar Ankle Fracture a Tertiary Care Experience - Najeeb Ullah,; Muhammad Suhail Amin,; Baryalai Khan,; Asad Moiz Hussain,; Muhammad Shoib,; Khushal Khan Kakar,; Sana Ullah Kakar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Ankle fractures, especially tri-malleolar fractures, are among the most frequent injuries to the lower extremities, affecting about 179 out of 100,000 individuals each year. Because of their complexity, these fractures provide serious complications for orthopedic surgeons. This work therefore analyzes tri-malleolar fractures to know the effect of prone position in relation to supine position while at the same time bearing in mind the characteristics of individual fracture, the surgeon and the patient. Methods: This comparative study was conducted at a tertiary care hospital, involving a cohort of 200 patients with diagnosed tri-malleolar ankle fractures. All participants registered to a tertiary care hospital for management of tri-malleolar ankle fractures were included in the study. Having distinguished patients who stayed in supine position during reduction from those in prone position, the authors proceeded to comparing results. In order to assess effectiveness of each position, radiographic assessment, clinical evaluation and surgical issues were reviewed. Results: Third malleolar fractures were effectively reduced in both supine and prone positions. While the prone position continued to be a dependable way to treat posterior malleolus fractures, the supine position offered improved anterior visibility and maybe decreased neurovascular problems. Positive results were obtained using both methods. Conclusion: For the purpose of reducing tri-malleolar fractures, the decision between prone and supine positions should be made individually. Both approaches can produce acceptable results; however, more investigation is required to improve position selection criteria by taking fracture features and patient-specific factors into account. Keywords: Tri-malleolar fracture, posterior malleolus, prone position, supine position, fracture reduction.